TECHNOLOGICAL SCAFFOLDING IN ELEMENTARY BILINGUAL ENGLISH INSTRUCTION: A MIXED‑METHODS APPROACH - Tiarnita Maria Sanjani; lya Sania Putri; Aulia Dea Ananda; Nia Diana Situmorang (Primary Education Journals (Jurnal Ke-SD-An), 2026)
This research examines the incorporation of technological support in elementary bilingual education to tackle the challenges of learning a second language in today’s digital world. Employing a qualitative literature review approach, the study explores how digital resources—including interactive multimedia, Augmented Reality, and automated feedback systems convert conventional instructional aid into a shared mediation network. The results reveal that technology acts as an “enhancing scaffold,” which lessens cognitive strain and promotes connections across languages through various modes of representation. Additionally, the research underscores that effective digital scaffolding necessitates a “gradual release of responsibility” to facilitate students’ transition from reliance on technology to independence in language use. The findings stress that the effectiveness of bilingual programs relies not only on the utilization of technology but also on intentional pedagogical strategies that harmonize human engagement with digital support.